Sosialisasi dan Gerakan Aksi Bersih Pantai Sebagai Upaya Mewujudkan Wisata Ramah Lingkungan di Pantai Cemara Desa Mojomulyo Puger - Nafi'ah, Mila (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2023)
Cemara Beach is one of the popular tourist destinations in Mojomulyo village, Puger District. Cemara Beach is unique from other beaches with cypress trees that live on the beach. However, this beach is experiencing quite serious problems with a lot of garbage scattered around. The types of garbage found organic and inorganic types come from three sources, namely, nature, people who throw garbage into the river, and also visitors who throw garbage carelessly around the beach. For this reason, the need for public awareness to maintain the cleanliness of tourist beaches by not littering. The purpose of this service activity is to realize Cemara beach as an environmentally friendly tourist beach by providing awareness of the cleanliness of the Cemara beach environment to the people of Mojomulyo Village. This method of service is the Asset Based Community Development (ABCD) approach. This service activity was carried out in Mojomulyo Village, Puger District, Jember Regency. The result of this service is that the CERIA program contains socialization activities carried out smoothly and in accordance with the success indicators that have been preloaded. Another activity, namely the beach clean action, managed to transport around 40 plastic garbage. The impact of this activity is to increase public awareness and concern in maintaining the beach environment which can later make the beach clean, comfortable, and increase tourist attraction to the beach.